THE EFFECT OF TASK GROUP GUIDANCE ON STUDENT RESILIENCE CLASS MTS NEGERI 1 GORONTALO CITY - Rena Madina; Nella Dasinsingon (International Journal of Innovations in Engineering Research and Technology, 2021)
This research is motivated by the symptoms that occur in MTSN I Gorontalo City, namely about the low resilience of grade VIll students. The purpose of this study was to determine the effect of task group guidance on student resilience. This research is a quasi-experimental research using a one group pre-test and post-test design. This study consists of two variables, namely variable X (Assignment Group Guidance) and Variable Y (Resilience) class VIII MTSN I Gorontalo City. The population in this study amounted to 391 students. This study was given for 8 treatments to a sample of 15 students. The sampling technique used was purposive sampling, namely the sampling technique with certain considerations. The data collection technique was a questionnaire technique about the Y variable (Resilience). student). The results of the study obtained an average pre-test value of 170.07 and an average post-test value of 197.73. The results of hypothesis testing obtained t count > t table, namely 4,546>1, 76. It can be concluded that there is an effect of task group guidance on resilience in class VIII students at MTSN I Gorontalo City.